2020
DOI: 10.1007/s00068-020-01494-y
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reliability of the Gehweiler classification and treatment strategies of isolated atlas fractures: an internet-based multicenter survey among spine surgeons

Abstract: Purpose Atlas (C1) fractures are commonly rated according to the Gehweiler classification, but literature on its reliability is scarce. In addition, evaluation of fracture stability and choosing the most appropriate treatment regime for C1-injuries are challenging. This study aimed to investigate the interobserver reliability of the Gehweiler classification and to identify whether evaluation of fracture stability as well as the treatment of C1-fractures are consistent among spine surgeons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…This is even more relevant when evaluating rare upper cervical spine injuries such as C1 and C2 ring injuries, which can be highly complex injuries that require accurate pattern recognition. 20 Furthermore, discussion on atlas injuries and C2 type B injuries is warranted given the moderate interobserver reliability when evaluated by orthopedic spine surgeons and neurosurgeons (the remaining injury subtypes received substantial or excellent interobserver reliability). Although the goal of an injury classification is to optimize its interobserver reliability (providing a framework for fa-cilitating future research, clinical discussion of injury patterns, and injury management guidance), the inherent rarity of certain injuries can make this challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is even more relevant when evaluating rare upper cervical spine injuries such as C1 and C2 ring injuries, which can be highly complex injuries that require accurate pattern recognition. 20 Furthermore, discussion on atlas injuries and C2 type B injuries is warranted given the moderate interobserver reliability when evaluated by orthopedic spine surgeons and neurosurgeons (the remaining injury subtypes received substantial or excellent interobserver reliability). Although the goal of an injury classification is to optimize its interobserver reliability (providing a framework for fa-cilitating future research, clinical discussion of injury patterns, and injury management guidance), the inherent rarity of certain injuries can make this challenging.…”
Section: Discussionmentioning
confidence: 99%
“…This is even more relevant when evaluating rare upper cervical spine injuries such as C1 and C2 ring injuries, which can be highly complex injuries that require accurate pattern recognition. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous atlas fracture classifications have been proposed, but they have primarily been designed for descriptive purposes 1,6. Recently, Laubach et al 21 found the Gehweiler classification had moderate interobserver reliability (κ=0.50) when evaluated by 20 members of the German Society for Spine Surgeons, which was similar to the interobserver reliability obtained in our study when evaluating the AO Spine Upper Cervical Injury Classification (range: κ=0.45–0.60 for type IIA–IIC injuries on AS1 and AS2). Therefore, it appears plausible the complexity of atlas injuries account for the moderate classification reliability regardless of the classification schema applied to these injuries 22…”
Section: Discussionmentioning
confidence: 99%
“…2 Although this may be partially due to the inherent complexity of atlas fractures given that the reliability of the Gehweiler classification (a descriptive classification for atlas injuries) was recently demonstrated as moderate (k=0.50), our study suggests that minimal differences in classification accuracy or reliability exist for IIA or IIC injuries. 12 Instead type IIB injuries, which can be treated with divergent management pathways (conservative versus operative), may be uncommonly encountered and require additional trauma experience or tailored education to optimize classification accuracy. 13 Additionally, if surgeons choose to supplement CT scans with magnetic resonance imaging (MRI), additional information may be obtained which could improve the classification accuracy.…”
Section: The Accuracy and Reliability Of Applying The Ao Spine Upper ...mentioning
confidence: 99%